Repetitively Coupled Chemical Reduction and Galvanic Exchange as a Synthesis Strategy for Expanding Applicable Number of Pt Atoms in Dendrimer-Encapsulated Pt Nanoparticles - Cho, Taehoon; Yoon, Chang Won; Kim, Joohoon (AMER CHEMICAL SOC, 2018)
In this study, we report the controllable synthesis of dendrimer-encapsulated Pt nanoparticles (Pt DENs) utilizing repetitively coupled chemical reduction and galvanic exchange reactions. The synthesis strategy allows the expansion of the applicable number of Pt atoms encapsulated inside dendrimers to more than 1000 without being limited by the fixed number of complexation sites for Pt2+ precursor ions in the dendrimers. The synthesis of Pt DENs is achieved in a short period of time (i.e., similar to 10 min) simply by the coaddition of appropriate amounts of Cu2+ and Pt2+ precursors into aqueous dendrimer solution and subsequent addition of reducing agents such as BH4-, resulting in fast and selective complexation of Cu2+ with the dendrimers and subsequent chemical reduction of the complexed Cu2+ while uncomplexed Pt2+ precursors remain oxidized. Interestingly, the chemical reduction of Cu2+, leading to the formation of Cu nanoparticles encapsulated inside the dendrimers, is coupled with the galvanic exchange of the Cu nanoparticles with the nearby Pt2+. This coupling repetitively proceeds until all of the added Pt2+ ions form into Pt nanoparticles encapsulated inside the dendrimers. In contrast to the conventional method utilizing direct chemical reduction, this repetitively coupled chemical reduction and galvanic exchange enables a substantial increase in the applicable number of Pt atoms up to 1320 in Pt DENs while maintaining the unique features of DENs.
Keywords: CATALYTIC-ACTIVITY; NANOCLUSTERS; SIZE; OXYGEN; NANOCOMPOSITES; TEMPLATES; ULTRAFAST; CLUSTERS